Carbon capture and biogas enhancement by carbon dioxide enrichment of anaerobic digesters treating sewage sludge or food waste - Bajón Fernández, Yadira; Soares, Ana; Villa, Raffaella; Vale, Peter C. J.; Cartmell, Elise (Elsevier Science B.V., Amsterdam., 2014)
The increasing concentration of carbon dioxide (CO2) in the atmosphere and the stringent greenhouse gases (GHG) reduction targets, require the development of CO2 sequestration technologies applicable for the waste and wastewater sector. This study addressed the reduction of CO2 emissions and enhancement of biogas production associated with CO2 enrichment of anaerobic digesters (ADs). The benefits of CO2 enrichment were examined by injecting CO2 at 0, 0.3, 0.6 and 0.9M fractions into batch ADs treating food waste or sewage sludge. Daily specific methane (CH4) production increased 11-16% for food waste and 96-138% for sewage sludge over the first 24h. Potential CO2 reductions of 8-34% for sewage sludge and 3-11% for food waste were estimated. The capacity of ADs to utilise additional CO2 was demonstrated, which could provide a potential solution for onsite sequestration of CO2 streams while enhancing renewable energy production.